Penalaan Pengontrol PID untuk Kecepatan Kecepatan Motor DC pada Robot Pengangkat Anak Timbangan - Syahwir, Irawati Dewi; Adoe, Cenneth Paolo Anderson Bai; Purwanto, Era; Yunanto, Prasetyo Wibowo; Wahyudi, Muhammad; Waras, Nandang Gunawan Tungga (Jurnal Otomasi Kontrol dan Instrumentasi, 2025)
The rapid development of technology allows human work to be replaced by robot technology. The most frequently used robot in industry is the robot arm. The robot arm can imitate the human arm's characteristics, so it is often used to help humans lift and move goods. With this principle, the robot arm can be used as a weight-lifting robot to aid in calibrating electronic scales. This paper analyzes the control of the DC motor on a weighing-scale lifting robot arm by optimizing the overshoot with PID (Proportional - Integral - Derivative) control. The PID Control test results on the DC motor rotation are stable at 100 rpm with a steady state error of 0%. The system's response to the DC motor has a settling time of 1,26 s and an overshoot of 2%.